2013
DOI: 10.5489/cuaj.546
|View full text |Cite
|
Sign up to set email alerts
|

A unique scrotal extratesticular epidermod cyst attached to the seminal vesicles

Abstract: E244 research researchCite as: Can Urol Assoc J 2013;7:E244-7. http://dx.doi.org/10.5489/cuaj.546 AbstractA 46-year-old man was admitted with a scrotal long standing painless mass. The workup included physical examination, alpha-fetoprotein (αFP) and beta-human chorionic gonadotropin (β-hCG) analyses, scrotal ultrasound, magnetic resonance imaging and urethrocystoscopy. Surgical exploration revealed a separate mass between the testes extending superiorly with a thin stalk. It was dissected easily to the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“… 7 Another case report described a scrotal epidermoid cyst attached to the anterior aspect of the seminal vesicles in the midline. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Another case report described a scrotal epidermoid cyst attached to the anterior aspect of the seminal vesicles in the midline. 8 …”
Section: Discussionmentioning
confidence: 99%
“…These tumors can occur at any age but are more common in the second to fourth decade of life [ 1 ]. They may be unilateral, bilateral, singular, or multiple and can be found at any place from the cranium to the anus in the midline [ 2 , 3 ]. The two main mechanisms by which the dermal epithelium reaches the deeper tissues and forms cysts are as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue lesions are better delineated on MRI. Therefore, it is preferable to use MRI instead of CT [ 2 ]. Pathologically, these lesions are squamous epithelium-lined cysts, containing keratin-like, cheesy white, flaky material, similar to those epidermoid cysts that occur intracutaneously [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scrotal and extra-testicular epidermoid cysts, as was the case in our patient, are very rare; the number of cases published in the English literature is less than 10. [2] Case Report A 36-year-old male presented in outpatient department with testicular discomfort and left scrotal swelling. He reported that the swelling appeared around two years back and has gradually progressed.…”
Section: Introductionmentioning
confidence: 99%